RULE OF LAW AND PUBLIC POWERS IN THE DIGITAL ERA. CYBERSOCIETY, CYBERCOMMUNITY, CYBERSTATE, CYBERSPACE: THIRTEEN THESIS (BioLaw Journal - Rivista di BioDiritto, 2022)
In this article, the author presents thirteen theses on the impact that artificial intelligence has and can have on a social and legal level. Starting with a description of the characters of cybersociety, he considers the potentialities and risks of the future use of AI, dealing with fundamental rights and balances of powers.
Keywords: artificial intelligence; cybersociety; digital society; fundamental rights